Наука охотничьему хозяйству УССР - Воиственский, М.А. (Вестник зоологии, 1971)
The article deals with the problem of main trends in scientific investigations, connecte d with the practice of hunting in the Ukraine. Brief information is given on scientific investigations of the hunting fauna of the Ukraine carried out for post-war years; the considerations are given concerning the nearest problems and prospects of the development of scientific investigations in the following principal trends: 1) development of the biological bases for organization of hunting farms (in particular the problems of hunting management); 2) studying of the population ecology of the most significant for the Ukraine species of hunting animals; 3) game breeding; 4) combination of the interests of agriculture and forestry with hunting under conditions of the Ukraine.